The complete chloroplast genome sequence of Styrax agrestis (Lour.) G. Don (Styracaceae) - Hongchao Wang; Yaoqin Zhang; Lili Tong; Yukun Tian; Xiaoyu Jiang; Xiaogang Xu (Mitochondrial DNA. Part B. Resources, 2021)
Styrax agrestis (Lour.) G. Don, is a deciduous species of Styracaceae with beautiful shape, drooping flowers, and blooming like snow. Here, we characterized the complete chloroplast (cp) genome of S. agrestis using next generation sequencing. The circular complete cp genome of S. agrestis is 157,893 bp in length, containing a large single-copy (LSC) region of 87,512 bp, and a small single-copy (SSC) region of 18,285 bp. It comprises 136 genes, including eight rRNA genes, 37 tRNAs genes, 90 protein-coding genes, and one pseudo gene. The GC content of S. agrestis cp genome is 36.96%. The phylogenetic analysis suggests that S. agrestis is a sister species to Styrax faberi in Styracaceae.